Relationship Between Women's Goals and Pregnancy Risk Behaviors - (:unkn) unknown (My University, 2019)
Among adult women, ages of 18 and 24 years old, a high percentage of the pregnancies that occur are unplanned (Finer & Zolna, 2016; Guttmacher Institute, 2016) and unplanned pregnancies have been linked to a greater risk of negative health outcomes for mothers and their infants (Dott, Rasmussen, Hogue, & Reefhuis, 2010; Hellerstedt, Pirie, Lando, Curry, McBride, Grothaus, & Clark Nelson, 1998; Kost, Landry, & Darroch, 1998; Mosher, Jones, & Abma, 2012; Pulley, Klerman, Tang, & Baker, 2002; Sharma, Synkewecz, Raggio, & Mattison, 1994; Weller, Eberstein, & Bailey, 1987). Work among adolescents has found a link between adolescents’ perception of the effect of pregnancy on their lives and academic goals and whether or not they were at risk of pregnancy/became pregnant (Bell, Glover, & Alexander, 2013; Gomez-Scott & Cooney, 2014; Jumping-Eagle, Sheeder, Kelly, & Stevens-Simon, 2008; Kogan et al., 2013; Luster & Small, 1994; Sipsma, Ickovics, Lewis, Ethier, & Kershaws, 2011). This work has not been extended into adults despite existing evidence that adult women’s family planning behaviors may be influenced by the same consideration of how pregnancy will influence their lives. The current research investigated whether younger college women’s perception of the effect pregnancy would have on their important goals predicted their family planning behaviors, including: whether or not participants were abstinent in the last three months, perceptions of the effectiveness of contraceptive used at last sexual intercourse, scientifically-established effectiveness of that contraceptive, and how consistently women used contraceptives (how often they had sex without contraceptives) in the last three months. Heterosexual female students, ages 18-24, from a large urban university completed the online Qualtrics survey (N = 204; sexually-active over the last three months n = 154). These young women did not have children and were not currently pregnant or trying to become pregnant. Women were asked to identify their important goals, assess the effect of pregnancy on their completion of this goal, and rate their motivation for completing each of these goals as part of the survey. These scores were used to calculate a score for the effect of pregnancy on their life goals. Women were also asked to provide information about whether they had had sex in the three months prior to the survey, what contraceptive they used at last sexual intercourse, how effective they believed this contraceptive option was for them, and the consistency of their contraceptive use over the last three months, their contraceptive self-efficacy, the availability of sexual partners, and their religiosity. Among women who have been sexually-active in the last three months, analysis found that women for whom the effect of pregnancy on life goals was more positive tended to be less consistent contraceptive users in the three months prior to the survey. For sexually-active women, however, perceived effectiveness of their contraceptive option and scientifically established effectiveness of their contraceptive option were not predicted by the effect of pregnancy on important life goals in analyses, potentially due to the high rate of effective contraceptive options used by this sample. Whether college women reported abstinence over the last 3 months was also not predicted by their score of the effect of pregnancy on their life goals, which may in part be due to the high number of participants (more than 90% reported access to insurance and effective contraceptive options). Future work is needed to further investigate the dynamic between the perceived influence of pregnancy on life goals and consistency of contraceptive behaviors in college women, as well as how this assessment of life goals may influence general family planning behaviors in other groups of women and in men. Physicians, other medical providers, and sexual health educators, however, may do well to include healthy pregnancy planning, and information on pregnancy avoidance, based on how women view the role of pregnancy in their lives rather than strictly on whether they are currently trying to get pregnant or report the wish to have a scientifically-established effective contraceptive option to avoid pregnancy. This is particularly true if that effective option is one which the user can easily stop using.
Keywords: contraceptives; family planning; life goals; pregnancy; self-efficacy